Media Photo Story dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Budi Febriyanto; Ari Yanto (Proceedings of The ICECRS, 2019)
At present the use of learning media is not optimal. Media that is widely used is only limited to visual print media so that learning still cannot bring out the curiosity of students during learning. Even though learning media is one of the most important elements to support the success of the learning process. In the process of Indonesian language learning in elementary school, students are required to be able to develop four language skills, listening, speaking, reading, and writing. The photo story media includes audio visual media that can help students master the four language skills. Photo story media is a picture of a story that has meaning, displayed through video shows using a computer or laptop device. The use of photo story media can stimulate the imagination of students and increase motivation in learning Indonesian. Thus, learning Indonesian in elementary schools by utilizing photo story media is able to accommodate learning to be more meaningful, stimulate the imagination of students, motivate learning activities and of course help students develop their language skills.